Des responsables d'équipe dans le déploiement d'un enseignement à distance : entre innovation, industrialisation et modèles de dissémination - Jean-Michel Gélis (Centre National d'Enseignement à Distance, 2015)
This paper deals with the deployment of distance learning systems in universities. We here explore a particular case, when an existing distance organization is deployed on courses of the same institution only available in face to face contexts, with an increase of the number of students and a new experience for teachers already very experimented for the face to face classes and nearly beginners in distance teaching. Specific actors, the team managers, played a key role in this deployment. They were volunteers and had to adapt the pedagogical model of distance learning to their teachings. They involved and managed a team of colleagues, "translating" the innovation process to their team. Our experience deals with innovation, industrialization and their models. In the first part, we recall some important theoretical frameworks, then we explain our methodology and finally we discuss our results, referring to the previous frameworks.